2010
DOI: 10.1007/s10682-010-9446-6
|View full text |Cite
|
Sign up to set email alerts
|

Complex environmental effects on the expression of alternative reproductive phenotypes in the bulb mite

Abstract: Understanding the evolution and maintenance of within-sex reproductive morphs, or alternative reproductive phenotypes (ARPs), requires in depth understanding of the proximate mechanisms that determine ARP expression. Most species express ARPs in complex ecological environments, yet little is know about how different environmental variables collectively affect ARP expression. Here, I investigated the influence of maternal and developmental nutrition and sire phenotype on ARP expression in bulb mites (Rhizoglyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(130 citation statements)
references
References 45 publications
(68 reference statements)
6
120
1
3
Order By: Relevance
“…However, Smallegange's (2011) results might align with ours, as the maternal effects detected by Smallegange (2011) would probably be detected as paternal effects in a diallel approach such as the one we used. The reason being that Smallegange's (2011) study also found a sire effect on the size of eggs produced by females.…”
Section: Maternal Effectssupporting
confidence: 73%
See 3 more Smart Citations
“…However, Smallegange's (2011) results might align with ours, as the maternal effects detected by Smallegange (2011) would probably be detected as paternal effects in a diallel approach such as the one we used. The reason being that Smallegange's (2011) study also found a sire effect on the size of eggs produced by females.…”
Section: Maternal Effectssupporting
confidence: 73%
“…However, Smallegange's (2011) results might align with ours, as the maternal effects detected by Smallegange (2011) would probably be detected as paternal effects in a diallel approach such as the one we used. The reason being that Smallegange's (2011) study also found a sire effect on the size of eggs produced by females. If a female's mate influences the size of her eggs, paternal effects could actually be the ultimate determining factor of egg size, as sires would actually be driving the differential allocation of resources into eggs by dams (Burley 1986).…”
Section: Maternal Effectssupporting
confidence: 73%
See 2 more Smart Citations
“…In many species, individuals develop profoundly different behavioral 269 repertoires or subsequent physical characteristics depending on aspects of state (e.g., 270 size) at a critical point in development (Emlen & Nijhout, 1999;Gross, 1985; 271 likelihood that they will develop into 'fighters' (Smallegange, 2011). This example is 288 based upon two extreme morphs whose divergence far outstrips anything seen in any 289 mammal, let alone humans.…”
Section: Deriving Information From the Environment To Predict The Futmentioning
confidence: 99%